Salvaging the trans-pacific partnership: Building blocks for regional and multilateral trade opening? - Matthias Helble (Asian Development Bank Institute (ADBI), 2017)
The high hopes that the Trans-Pacific Partnership (TPP) would open up trade across the Pacific were dashed by the decision of the new US Government under President Trump to withdraw from the agreement in January 2017. Despite being controversial, the TPP had been recognized as an agreement that substantially updated and extended international trade rules responding to new technological developments and economic realities. It was thus lauded by some as the first true 21st century trade agreement. The United States' withdrawal from TPP gives the agreement an uncertain future. Yet, we argue in this paper that some achievements of the TPP might not be lost. The TPP offers important lessons for other ambitious regional trade deals both in terms of process and content. Furthermore, several chapters of the TPP can become blueprints for ongoing and upcoming negotiations at the multilateral level. A one-to-one transposition of TPP provisions into the multilateral trade agreement is unlikely, yet certain provisions could serve as valuable aspiration for future multilateral trade talks.
Keywords: F10; 330; Industry and trade